Risk aversion in the use of complex kidneys in paired exchange programs: Opportunities for even more transplants?. Issue 7 (2nd March 2022) - Roll, Garrett R.; Cooper, Matthew; Verbesey, Jennifer; Veale, Jeffrey L.; Ronin, Matthew; Irish, William; Waterman, Amy D.; Flechner, Stuart M.; Leeser, David B.
Abstract : This retrospective review of the largest United States kidney exchange reports characteristics, utilization, and recipient outcomes of kidneys with simple compared to complex anatomy and extrapolates reluctance to accept these kidneys. Of 3105 transplants performed, only 12.8% were right kidneys and 23.1% had multiple renal arteries. 59.3% of centers used fewer right kidneys than expected and 12.1% transplanted zero right kidneys or kidneys with more than 1 artery. Five centers transplanted a third of these kidneys (35.8% of right kidneys and 36.7% of kidneys with multiple renal arteries). 22.5% and 25.5% of centers currently will not entertain a match offer for a left or right kidney with more than one artery, respectively. There were no significant differences in all‐cause graft failure or death‐censored graft loss for kidneys with multiple arteries, and a very small increased risk of graft failure for right kidneys versus left of limited clinical relevance for most recipients. Kidneys with complex anatomy can be used with excellent outcomes at many centers. Variation in use (lack of demand) for these kidneys reduces the number of transplants, so systems to facilitate use could increase demand. We cannot know how many donors are turned away because perceived demand is limited. Abstract : The low acceptance rate of kidneys with complex anatomy in a national kidney exchange program, in spite of excellent long‐term outcomes, evidences lackluster demand that may reduce the number of accepted donors and, in turn, the number of transplants